2011
DOI: 10.1016/j.ejcts.2011.02.077
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered vascular graft remodeling in a growing lamb model: expression of matrix metalloproteinases

Abstract: MMPs are up-regulated in vitro by dynamic culture conditions and could contribute to increased matrix remodeling, native analogous tissue formation and functional growth of TEVGs in vivo. Monitoring of MMP activity, for example, by molecular imaging techniques, may enable the non-invasive assessment of functional tissue quality in future clinical tissue-engineering applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
(46 reference statements)
2
28
0
Order By: Relevance
“…Prior post-mortem examination of TEVGs implanted in a murine model has demonstrated progressively higher MMP-2 expression over a 4-week time course following TEVG implantation, while MMP-9 expression peaked at 1 week after surgery and significantly decreased by 4 weeks. 6 The elevated expression of MMP-2 within a murine model of TEVG is consistent with the post-mortem findings of Cummings et al, 7 who observed elevated MMP-2 expression in a lamb model of TEVG implantation; however, MMP-9 expression also remained elevated for 80 weeks following implantation. These results suggest that MMPs may play a role in the remodeling of TEVGs and that this process may be prolonged for many months following implantation.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Prior post-mortem examination of TEVGs implanted in a murine model has demonstrated progressively higher MMP-2 expression over a 4-week time course following TEVG implantation, while MMP-9 expression peaked at 1 week after surgery and significantly decreased by 4 weeks. 6 The elevated expression of MMP-2 within a murine model of TEVG is consistent with the post-mortem findings of Cummings et al, 7 who observed elevated MMP-2 expression in a lamb model of TEVG implantation; however, MMP-9 expression also remained elevated for 80 weeks following implantation. These results suggest that MMPs may play a role in the remodeling of TEVGs and that this process may be prolonged for many months following implantation.…”
Section: Introductionsupporting
confidence: 86%
“…Two previous studies have quantified MMP activity within TEVGs implanted as IVC interposition grafts; however, these studies required histologic evaluation of explanted neotissue. 6,7 In the present study, we sought to evaluate the feasibility of noninvasive assessment of MMP activity in a clinically relevant large animal model of TEVG implantation. We observed elevated MMP activity within the region of TEVG implantation at 6 months following implantation using in vivo SPECT/CT imaging (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For pre-clinical evaluation, tissue engineered constructs and their remodeling are typically tested in healthy animals [2830]. However, there are great expectations that TE and regenerative medicine research will offer solutions for patients affected by the cardiovascular complications of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous long-term safety and efficacy assessment in vivo must be completed to evaluate time-dependent durability of bioengineered vascular grafts because in vitro studies alone or short-term in vivo experiments do not capture time-dependent degeneration of the implanted material. Despite this need, very few studies have critically assessed long-term (defined as ≥3 months for small animals,[5] ≥12 months for large animals[10] and humans[11]) safety and efficacy of bioengineered vascular grafts in vivo . Although common evaluative end-points predominantly focus on graft stenosis due to neointimal hyperplasia or intravascular thrombosis, intra-graft calcification is often overlooked despite its importance in vascular tissues such as biological heart valves,[12, 13] smooth muscle biology,[14] and arterial mineralization in patients with vascular disease, diabetes, and chronic kidney failure (patients likely to be recipients of vascular grafts).…”
Section: Introductionmentioning
confidence: 99%